Broadband metamaterial absorber based on hybrid multi-mode resonance in mid-wave and long-wave infrared region - Xiaoyan shi; Enzhu Hou; Zhongzhu Liang; Shoutao Zhang; Rui Dai; Wei Xin; Dejia Meng; Hua Liu; Haiyang Xu; Yichun Liu (Results in Physics, 2022)
The infrared radiation of the target and scene needs to be transmitted through the surface atmosphere, and it can be detected by infrared thermal imaging equipment. The mid-wave infrared band (MWIR, 3–5 μm) and the long-wave infrared band (LWIR, 8–14 μm) are two atmospheric windows for heat transmission and are the principal operating band of infrared equipment. This paper proposed a broadband metamaterial absorber based on hybrid multi-mode resonance in the MWIR and LWIR. Metamaterial absorber with rectangular grating structure achieves a total of six absorption peaks with high absorption in the MWIR and LWIR. The proposed absorber is scalability in the MWIR and LWIR by tuning the structural parameters. And we designed six absorption peaks to achieve a broadband absorber based on the combined action of propagating surface plasmons (PSP), localized surface plasmons (LSP), and Fabry–Pérot (FP) resonance modes. The average absorption rate of the MWIR is 52 %, and the average absorption rate of the LWIR is 86 %. The geometry of the absorber structure is relatively large, which facilitates fabrication and integration. Although, in terms of its resonance mechanism, the absorption is directly related to the incident angle. However, the metamaterial absorber maintains good wide-angle characteristics when the incident angle is ± 45°. Therefore, the proposed dual-band absorbers in the MWIR and LWIR will have great application potential in infrared detection devices.